URGENSI PERLINDUNGAN HUKUM TERHADAP WHISTLEBLOWER DALAM UPAYA PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Nabila Azzahra; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2021)
Corruption is still a serious problem in Indonesia. This criminal act caused significant losses to state finances. Law enforcement for criminal acts of corruption done conventionally so far has proven to experience various disease resistance. Not a few cases have run aground in the middle of the road due to the absence of witnesses to support the duties of law enforcement officials. In its development, the term whistleblower is known as a criminal act of corruption. Assessed from a terminological perspective, a whistleblower is defined as someone who discloses a fact. In Indonesia whistleblower is a criminal act that reports and reports certain crimes and is not part of the crime it reports. In principle, whistleblowers can play a major role in exposing corrupt practices of public institutions. However, due to the lack of legal protection for whistleblowers in Indonesia, a whistleblower can be threatened physically, psychologically or at work because of his report or testimony of the allegations and crimes that have occurred. For this reason, in order for the practice of reporting and disclosing facts by whistleblowers to run more effectively, a concept of regulatory protection for whistleblowers in Indonesia is needed. As explained, this study aims to examine the form of legal protection for whistleblowers from a normative perspective and its implementation and also to study the practice of legal protection for whistleblowers in several countries to obtain the ideal legal protection concept for whistleblowers in Indonesia for the future.